Moving the Customer Experience Field Forward: Introducing the Touchpoints, Context, Qualities (TCQ) Nomenclature. (November 2020) - De Keyser, Arne; Verleye, Katrien; Lemon, Katherine N.; Keiningham, Timothy L.; Klaus, Philipp
In response to initial voices that put the customer experience (management) (CX(M)) movement into question, this article aims to introduce a formal nomenclature to push the CX(M) field toward a more mature state. First, drawing from an inductive analysis of 143 CX(M) papers, the authors identify 12 basic CX components that aggregate into three overarching building blocks—touchpoints (T, i.e., points of interaction between the customer and brand/firm), context (C, i.e., situationally available resources internal and/or external to the customer), and qualities (Q, i.e., attributes that reflect the nature of customer responses and reactions to interactions with the brand/firm). The TCQ nomenclature offers a language to make CX actionable, moving beyond the breadth of the current definition and frameworks by disentangling CX into small bite-sized chunks (i.e., the CX components) that any academic and practitioner, regardless of their discipline, may understand and use to discuss and manage CX. Second, using the TCQ nomenclature, the authors assess the current state of the CX(M) literature and identify mature (e.g., firm-controlled touchpoints and cognitive and emotional qualities associated with CX) and underdeveloped (e.g., nonfirm controlled touchpoints and the market and environmental context in which CX emerges) areas ripe for future research. In addition, they also provide a set of recommendations to strengthen the methodological rigor of the field. Third, the TCQ nomenclature may support managers in auditing their current CXM practices and/or serve as a basis for CX design and innovation.